Characterization of sand convective motions at a vertical wall subjected to long-term cyclic loading - Guan, Dawei (2022)
By conducting a two-dimensional experimental study, this paper aims to enhance the understanding of the mechanism of sand convective motions in the vicinity of a wall subjected to long-term cyclic lateral loadings. The experimental tests were conducted in a rectangular sandbox with a transparent front-wall, through which the process of sand particle motions could be recorded by using a high-resolution digital camera. The images were processed with a high time-resolved PIV (Particle Image Velocimetry) system. Based on the experimental data, this work (1) presents the sand flow field in the convective zones; (2) provides means to describe the convection mechanism; (3) proposes the relationships between the loading conditions and dimensions of the region with intense sand movement; and (4) elaborates the similarity of the sand flow velocity structure within the sand convective zones.